Effects of Ethics and Performance Management on Organizational Performance in the Public Sector. (3rd July 2020) - Khaltar, Odkhuu; Moon, M. Jae
Abstract : This study empirically tests the effects of ethics management, performance management, and transformational leadership on organizational performance in Korean public organizations by using Structural Equation Modeling (SEM) on data collected from 270 public employees. In examining the relationships among ethics management; performance management; transformational leadership; and organizational performance, this research also explores the mediating roles of organizational commitment and ethical performance that contribute to organizational performance. Informal ethics management and transformational leadership are found to increase organizational performance by reducing unethical behavior and improving organizational commitment in public agencies.